Computed tomographic localization of infraorbital foramen position and correlation with the age and gender of Iraqi subjects - Mohammed, Amaal I; Fatah, Ahlam A (Journal of Baghdad College of Dentistry, 2013)
Background: The Infraorbital foramen is an anatomical structure with an important location in the maxilla, position of foramen in maxillofacial area is necessary in clinical situation requiring regional nerve blocks that are performed in children undergoing facial surgeries to avoid injury to corresponding nerve. The aim of study was to determine the position of the Infraorbital foramen and to correlate Infraorbital foramen position with age and gender using computed tomography. Subjects, Materials, and Methods: The sample consist of prospective study for 50 Iraqi subjects (21 male and 29 female) with age ranged from (5-17) years. The examination was performed on Multi – Slice Spiral Tomography scanner in Al-Karakh General Hospital. Using sagittal and coronal sections including right and left sides and the following measurements were done: 1. The distance from crista galli to the midpoint of fusion of hard palate(Midline of the patient) in the coronal section. 2. The distance from mid line to the infraorbital foramen, in the coronal section for both sides right and left. 3. The distance from sella turcica to the infraorbital foramen, in sagittal section for both sides right and left. 4. The distance from nasion to the infraorbital foramen, in coronal section for both sides right and left. Results: The partial regression coefficient for each year increase in age the linear measurements (midline-infraorbital foramen) (nasion-infraorbital foramen) and (vertical distance from nasion meeting the horizontal line from infraorbital foramen to midline) are expected to significantly increase after adjusting for confounding effect of gender. From multiple linear regression model designed in this study two mathematical formulae were derived for correlation of infraorbital foramen position with the age and gender:- Y1 [Linear measurement (Midline-Infraorbital foramen) mm] = 19.56 + (1.02 x gender) + (0.53x age in years). Y2 [Linear measurement (vertical distance from nasion meeting the horizontal line from Infraorbital foramen to midline)] = 28.42 + (2.5 x gender) + (0.30 x age in years). Conclusions: Computed tomography scan information facilitates the localization of infraorbital foramen position for successful access of the needle in infraorbital nerve block in children of different age and gender.